ANÁLISE ECONÔMICA E ÍNDICES DE COMPETIÇÃO DO CONSÓRCIO DE RABANETE E RÚCULA - BARROS FILHO, Luís Gustavo Silva; GOMEZ, Aurélio Luís Carpinedo; RODRIGUES, Pedro Henrique Dias; MARCELINO, Adriele Ferreira; DA SILVA, Maiele Leandro (ANAIS DO ENIC, 2025)
-